Phoenix from the Ashes: Physician Burnout in Pakistan - Hashmi, Ali Madeeh; Ahmed, Bilal; Nawal, Aiman; Asif, Aftab (Journal of Pakistan Psychiatric Society, 2021)
Burnout is common and globally prevalent, especially in the healthcare community. COVID19 has aggravated the already high prevalence of burnout leading to multiple negative consequences on physician health as well as healthcare delivery. This review paper examines the prevalence of burnout globally with a special focus on Pakistani healthcare workers specially physicians. An analysis of the psychological causes of burnout and some remedies are also suggested along with some vignettes illustrating this phenomenon.